140 Making every day count for patients in an acute hospital at the end of life: silver to gold bed days. Issue Volume 8: Issue (2018)Supplement 1 (1st March 2018) - Hayle, C; Given, E; Hayes, A; Houghton, B; Latten, R; Maxwell, M; Pattullo, A; Purewal, G; Shouls, S; Sanders, C
Abstract : Background: Wirral University Teaching Hospitals NHS FT serves a population of 330, 000. Patients who subsequently die in hospital spend 21 days (mean) of their last 100 days of life in hospital. When time is so precious, it is crucial that every day spent in hospital 'counts'. Inpatient specialist palliative care and end of life care provisions was fragmented. The aim was to improve care and cohesiveness by putting patient's wishes at the centre of clinical process. Methods: The 'red to green days' concept (developed for Safer Patient Flow) was adapted to focus on patient experience of care. At the start of the day a board round assesses 'what matters most today' for each patient, with agreed actions across the team. The patient's day starts as silver and is then recorded as 'gold' only if progress is made against the patient's expressed wishes. A silver day means a patient receives high quality care, but no action to achieve wishes. The team applied 'Plan Do Study Act' methods to develop this approach from concept to practice. Results: Patients' wishes were more consistently understood and met. Examples include: obtaining a wig, a urinary catheter, complex spiritual care, wedding ceremony, rapid discharge, hospice bed, physical symptom control. The focus on 'what matters most' to patients increased team cohesiveness, greater peer support and shared responsibility rather than individual caseloads. Performance was monitored using Statistical Process Control and ongoing analysis of barriers to achieving a gold day. There is an association between patient flow and the ability of the SPC team to meet patient wishes. Conclusions: A singe focus on patients' wishes and what matters to them helps team working together to meeting these goals. Collecting evidence on why patients are unable to achieve their wishes supports thematic learning to guide future commissioning and service developments.